1999
DOI: 10.1081/ada-100101849
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Drug Network, and Their Synergistic Effect on Needle-Sharing Behavior Among Street Injection Drug Users

Abstract: In this study, we examined the relationship between depressive symptoms and needle-sharing behavior in a community sample of intravenous drug users (N = 499) in Baltimore, Maryland. Based on the polytomous logistic regression, higher depressive symptoms were positively associated both with needle sharing after cleaning with bleach and with needle sharing without first cleaning with bleach at the bivariate analyses. This relationship remained significant (OR = 1.66) even after adjusting for demographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 17 publications
9
49
1
2
Order By: Relevance
“…We found that men experienced HIV risk behaviors as well, with increased homelessness and incarceration relative to women, though these differences were attenuated after adjustment for confounders; indeed, the constellation of psychosocial issues including depression was greater among women than men, as other authors have found. 7,41,[44][45][46] Other authors have noted differences in injection rituals, practices, and injection partner selection between men and women 7,10,14,15,17,39 ; identification of needs that are fulfilled by such practices and that drive their selection, may inform development of innovative prevention approaches developed specifically for women. Our findings echo those of other authors, with some differences: in a convenience sample of younger IDU, Doherty et al 15,16 found women had elevated risk of HIV and while they had similar patterns of injection initiation, women were no more likely to be injected by sex partners at injection initiation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that men experienced HIV risk behaviors as well, with increased homelessness and incarceration relative to women, though these differences were attenuated after adjustment for confounders; indeed, the constellation of psychosocial issues including depression was greater among women than men, as other authors have found. 7,41,[44][45][46] Other authors have noted differences in injection rituals, practices, and injection partner selection between men and women 7,10,14,15,17,39 ; identification of needs that are fulfilled by such practices and that drive their selection, may inform development of innovative prevention approaches developed specifically for women. Our findings echo those of other authors, with some differences: in a convenience sample of younger IDU, Doherty et al 15,16 found women had elevated risk of HIV and while they had similar patterns of injection initiation, women were no more likely to be injected by sex partners at injection initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Female IDUs' self-efficacy for safer drug injection may be inhibited by a violent and/or controlling partner, thereby influencing syringe sharing. Similarly, studies have identified depression as a correlate of both syringe sharing (Johnson et al 2002;Mandell et al 1999;Perdue et al 2003;Stein et al 2004;Strathdee et al 1997) and IPV (Bonomi et al 2006;Lehrer et al 2006), suggesting its role as a mediator of the relationship between IPV and HIV risk. Finally, IPV has been associated with reductions in self-esteem (Zlotnick et al 2006), perhaps due to the social isolation resulting from victimization (Miller 1999.…”
Section: Introductionmentioning
confidence: 95%
“…32,37,38 Poor coping behaviors such as use of drugs or alcohol are common and are associated with more risky behaviors for HCV infection. [39][40][41] A metaanalysis of interventions to prevent HCV seroconversion among IDUs indicated that multidisciplinary programs may be more beneficial than single intervention programs. 42 For instance, an HCV intervention program for homeless youth, focusing on problem solving skills and strategies to remain HCV uninfected, produced a 29 % greater decline in overall injection risk 6 months post-intervention relative to the control group.…”
Section: Homelessness Intensifies Hcv Risk Behaviorsmentioning
confidence: 99%